Risk factors associated with depression in pregnant women: an integrative literature review (Research, Society and Development, 2020)
The purpose of this article is to identify and analyze the risk factors related to depression in pregnancy and, therefore, the nursing care provided. This is a bibliographic review study using the integrative review method with a quantitative approach, carried out by means of bibliographic survey in the following databases: Lilacs, Bdenf and Medline. The inclusion criteria were original research, cohort study, case control study, randomized clinical trial, in Portuguese, English and Spanish, which answered the research question and excluded duplicate studies, unavailable in full for reading, theses, dissertations, monographs and manuals. The initial sample consisted of 295 studies, after reading the titles and abstracts, 16 articles remained to compose the final sample. The results obtained with this research showed the prevalence of certain risk factors for gestational depression in the articles. It was observed that lack of social and family support, cultural factors, secondhand smoke, use of alcohol and tobacco and hyperemesis gravidarum were the most prevalent subjects in the studies. Nursing has a fundamental role in all assistance and must observe the presence of depressive symptoms through active and qualified listening in order to prevent and treat such occurrences.